Are Metacognitive Beliefs and Cognitive Flexibility Associated With Cannabis Use Disorder In Adolescents? A Case–Control Study - Neval Kızıl; Masum Öztürk; Fatma Subaşı Turgut; Yağmur Soysal; Ayfer Gözü Pirinççioğlu (Clinical Psychology & Psychotherapy, 2026)
ABSTRACT Objective Cannabis is among the most commonly used substances by adolescents and is frequently associated with the development of addiction. Various individual, environmental and psychological factors are associated with the onset and maintenance of cannabis use disorder (CUD). Our study aimed to compare levels of depression, anxiety, stress, perceived cognitive flexibility and metacognitive beliefs in adolescents diagnosed with CUD with those in a healthy control (HC) group. Another objective was to investigate the relationship between CUD severity and these parameters within the CUD group. Methods Our study included a total of 69 patients aged 12–18 years with a diagnosis of CUD and 83 age‐ and gender‐matched HC subjects. Participants completed the Sociodemographic Data Form, Addiction Profile Index (API), Metacognition Scale–Children and Adolescents Form (MCQ‐C), Cognitive Flexibility Scale (CFS) and Depression‐Anxiety‐Stress Scale (DASS‐21). Results Patients with CUD had significantly higher MCQ‐C total scores ( p = 0.033), higher levels of superstition‐punishment‐responsibility beliefs ( p = 0.001) and higher DASS‐21 scores ( p < 0.001) compared to the HC group. Perceived cognitive flexibility was significantly lower in the CUD group ( p < 0.001). Higher levels of negative metacognitive beliefs ( p = 0.006) and total emotional symptoms in the CUD group were positively associated with CUD severity ( p < 0.001, F = 7.512, R 2 = 0.365). Conclusion These results demonstrate the significant association between metacognitive beliefs, accompanying emotional symptoms and perceived cognitive flexibility in adolescents with CUD. Our findings highlight the importance of addressing these psychological correlates during treatment planning. Interventions targeting not only substance use reduction but also these associated cognitive and metacognitive factors may be beneficial for improving treatment outcomes.